Investigation of the sensitivity of turbulent closures and coupling of hybrid RANS‐LES models for predicting flow fields with separation and reattachment. (4th October 2016) - Kumar, G.; Lakshmanan, S. K.; Gopalan, H.; De, A.
Summary: Hybrid models have found widespread applications for simulation of wall‐bounded flows at high Reynolds numbers. Typically, these models employ Reynolds‐averaged Navier–Stokes (RANS) and large eddy simulation (LES) in the near‐body and off‐body regions, respectively. A number of coupling strategies between the RANS and LES regions have been proposed, tested, and applied in the literature with varying degree of success. Linear eddy‐viscosity models (LEVM) are often used for the closure of turbulent stress tensor in RANS and LES regions. LEVM incorrectly predicts the anisotropy of Reynolds normal stress at the RANS‐LES interface region. To overcome this issue, use of non‐linear eddy‐viscosity models (NLEVM) have started receiving attention. In this study, a generic non‐linear blended modeling framework for performing hybrid simulations is proposed. Flow over the periodic hills is used as the test case for model evaluation. This case is chosen due to complex flow physics with simplified geometry. Analysis of the simulations suggests that the non‐linear hybrid models show a better performance than linear hybrid models. It is also observed that the non‐linear closures are less sensitive to the RANS‐LES coupling and grid resolution. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this study, a generic non‐linear blended modeling framework for performing hybrid RANS‐LES simulations is proposed and flow over the periodic hills is used as the test case for model evaluation. Analysis of the simulations suggests that the non‐linear closures are less sensitive to the RANS‐LES coupling method and grid resolution. Also, good agreement has been found for flow statistics compared with the existing experimental data for simulations performed using NSST‐Blended at higher Reynolds number.